Snapshot of the Genome of the Pseudo-T-Even Bacteriophage RB49 - Desplats, Carine (American Society for Microbiology, 2002)
RB49 is a virulent bacteriophage that infects Escherichia coli. Its virion morphology is indistinguishable from the well-known T-even phage T4, but DNA hybridization indicated that it was phylogenetically distant from T4 and thus it was classified as a pseudo-T-even phage. To further characterize RB49, we randomly sequenced small fragments corresponding to about 20% of the ≈170-kb genome. Most of these nucleotide sequences lacked sufficient homology to T4 to be detected in an NCBI BlastN analysis. However, when translated, about 70% of them encoded proteins with homology to T4 proteins. Among these sequences were the numerous components of the virion and the phage DNA replication apparatus. Mapping the RB49 genes revealed that many of them had the same relative order found in the T4 genome. The complete nucleotide sequence was determined for the two regions of RB49 genome that contain most of the genes involved in DNA replication. This sequencing revealed that RB49 has homologues of all the essential T4 replication genes, but, as expected, their sequences diverged considerably from their T4 homologues. Many of the nonessential T4 genes are absent from RB49 and have been replaced by unknown sequences. The intergenic sequences of RB49 are less conserved than the coding sequences, and in at least some cases, RB49 has evolved alternative regulatory strategies. For example, an analysis of transcription in RB49 revealed a simpler pattern of regulation than in T4, with only two, rather than three, classes of temporally controlled promoters. These results indicate that RB49 and T4 have diverged substantially from their last common ancestor. The different T4-type phages appear to contain a set of common genes that can be exploited differently, by means of plasticity in the regulatory sequences and the precise choice of a large group of facultative genes.